(untitled) (Physical Education, Health and Social Sciences, 2025)
Violence refers to “behavior involving physical force intended to hurt, damage, or kill someone or something.” Workplace violence, also known as occupational violence, is an increasing global problem that threatens the safety of healthcare professionals and communities worldwide. To determine the prevalence of workplace violence among female nurses working in a tertiary healthcare setting. A cross-sectional study was conducted at a tertiary care hospital in Bahawalpur over four months, from September 2025 to November 2025. A convenience sampling technique was used. A validated questionnaire was administered after obtaining informed consent. Sample size was calculated using a standard formula with a 95% confidence level. Data were analyzed using SPSS version 26. Results are presented as frequencies and percentages. A total of 80 female nurses participated. The majority (92.5%) reported experiencing workplace violence. Verbal abuse was the most common type (66.7%), followed by physical violence (22.5%), bullying/mobbing (3.7%), and sexual harassment (1.3%). Workplace violence is highly prevalent among female nurses in tertiary care. Immediate preventive strategies, such as zero- tolerance policies, staff training, improved security, and supportive reporting systems, are essential to ensure a safe working Environment.